A Brief Overview of Adolescent Developmental Problems in Hong Kong. (4th September 2011) - Shek Shek, Daniel T. L. Daniel T. L.; Keung Ma Keung Ma, Hing Hing; Sun Sun, Rachel C. F. Rachel C. F.
Abstract : Several adolescent developmental problems in Hong Kong are briefly reviewed in this paper. First, rising adolescent substance abuse trends are described. Second, Internet use problems and Internet addiction among young people are examined. Third, worrying trends in adolescent sexuality are identified. Fourth, phenomena on bullying among young people are reviewed. Finally, phenomena related to adolescent materialistic orientation are focused upon. With reference to these adolescent developmental problems, possible solutions are briefly discussed particularly with reference to the ecological perspective. It is argued that the related scientific literature provides useful pointers for designing the curriculum in the extension phase of the Project P.A.T.H.S. in Hong Kong.